Kinetic Study of Kapok Seed Oil Esterification using BMIM-PF6 Catalyst - Bagus Agang Sudrajat; Widayat Widayat; Ngurah Widiantara; Hantoro Satriadi; Maria Siahaan; Wira Pinem (Dept. of Chemical Engineering, Diponegoro University, 2020)
Biodiesel offers better combustion efficiency, lower sulfur content and aromatic compounds, higher cetane numbers than diesel fuel, biodegradable and renewable properties that are not possessed by conventional fuels such as diesel fuel. This study aims to study the modeling of esterification process of Kapok seed oil using 3 % liquid ionic catalyst 1-Butyl-3-MethydidazoliumHexafluorophosphate (BMIM-PF6). The validation results of reaction kinetic models for experiments and simulations provide an adjacent correlation value, that is R2 = 0.99526, with the rate constant value (k) based on experimental data are 0.003815 L/mol.s and 0.0038 L/mol.s for the simulation data. Based on the simulation results, the proper reaction order for this esterification reaction is the first order reaction equation with a value of R2 = 0.99526, while the second order reaction gives the value R2 = 0.89453. The reaction kinetics parameters obtained from the experimental results are A = 0.012 L/mol.s and -Ea = -0.437 kJ/mol, while the reaction parameters of the simulation are A = 1.0384 L/mol.s and -Ea = -89.5 kJ/mol.Keywords: Esterification, Ionic Liquid Catalyst, Kinetic